Prospective study of Q-switched Nd:YAG laser treatment of hyperpigmented split-thickness skin grafts - Tonaree W. (2023)
Hyperpigmentation of split-thickness skin grafts (STSGs) is commonly found among Asians, and it is also challenging to treat. Although the 1064-nm Q-switched Nd:YAG laser has been used as a standard treatment for skin hyperpigmented lesions, there are limited number of reports focusing on the treatment of hyperpigmentation of STSGs. We aimed to evaluate the efficacy of 1064-nm Q-switched Nd:YAG laser for treatment of hyperpigmented STSGs. Half of each STSGs was treated with the 1064-nm Q-switched Nd:YAG laser, while the remaining was left untreated as comparison. The laser was applied for 4 times with 2–4-week interval. The treatment outcomes were compared by measurement of melanin index, erythema index, and photographs of STSGs at prior to enrollment, before each treatment session, and after 1 month of treatment completion. Five patients with 11 skin graft lesions were enrolled. The melanin index was significantly improved after the 2nd session and after treatment completion in laser-treated area (p = 0.006 and p = 0.001, respectively). There was non-significant difference in erythema index. The photographic comparison showed brightened of laser-treated area after treatment completion and improved skin texture. The 1064-nm Q-switched Nd:YAG laser can significantly reduce melanin index of STSGs and can be an alternative treatment for hyperpigmentation of STSGs.